Identification of DLD, by immunoproteomic analysis and evaluation as a potential vaccine antigen against three Vibrio species in Epinephelus coioides. Issue 9 (24th February 2016) - Pang, Huanying; Chen, Liming; Hoare, Rowena; Huang, Yucong; ZaoheWu,; Jian, Jichang
Abstract: Vibrio spp. represent a serious threat to the culture of Epinephelus coioides (Orange-spotted Grouper) in Southeast Asia. In this study we used two-dimensional electrophoresis (2-DE) and Western blotting to identify common immunogenic proteins of Vibrio alginolyticus, Vibrio harveyi and Vibrio parahaemolyticus. Membranes were probed with orange-spotted grouper anti- V. alginolyticus sera and accordingly 60, 58 and 48 immunogenic protein spots were detected. By matching analysis for the three Western blotting membranes, 6 cross immunogenic spots for the three Vibrio species were identified. They were Outer membrane protein W (OmpW), dihydrolipoamide dehydrogenase (DLD), succinate dehydrogenase flavoprotein subunit(SDHA), elongation factor Ts(Ts), peptide ABC transporter periplasmic peptide-binding protein and phosphoenolpyruvate carboxykinase(PEPCK). One of the proteins, DLD, was used to evaluate the cross protective function for E. coioides with a bacterial immunization and challenge method. The relative percent survival rate of E. coioides against V. alginolyticus, V. harveyi and V. parahaemolyticus was 90%, 86% and 80%, respectively. This work may provide potential cross protective vaccine candidate antigens for three Vibrio species, and DLD may be considered as an effective cross-protective immunogen against three Vibrio species.